Single anthocyanins effectiveness modulating inflammation markers in obesity: dosage and matrix composition analysis - Fragoso-Medina, Jorge Alberto; López Vaquera, Selma Romina; Domínguez-Uscanga, Astrid; Luna-Vital, Diego; García, Noemí (Frontiers in Nutrition, 2023)
Anthocyanins (ACNs) are phytochemicals with numerous bioactivities, e.g., antioxidant and anti-inflammatory. Health benefits from consuming ACN-rich foods, extracts, and supplements have been studied in clinical trials (CT). However, the individual effect of single ACNs and their correlation with doses and specific bioactivities or molecular targets have not been thoroughly analyzed. This review shows a recompilation of single anthocyanins composition and concentrations used in CT, conducted to investigate the effect of anti-inflammatory derivates of obese condition. Single anthocyanin doses with changes in the levels of frequently monitored markers were correlated. In addition, the analysis was complemented with reports of studies made in vitro with single ACNs. Anthocyanins’ efficacy in diseases with high baseline obesity-related inflammation markers was evidenced. A poor correlation was found between most single anthocyanin doses and level changes of commonly monitored markers. Correlations between cyanidin, delphinidin, and pelargonidin derivatives and specific molecular targets were proposed. Our analysis showed that knowledge of specific compositions and anthocyanin concentrations determined in future studies would provide more information about mechanisms of action.